Discovery of novel Mnk inhibitors using mutation‐based induced‐fit virtual high‐throughput screening. (4th August 2019) - Mishra, Rama K.; Clutter, Matthew R.; Blyth, Gavin T.; Kosciuczuk, Ewa M.; Blackburn, Amy Z.; Beauchamp, Elspeth M.; Schiltz, Gary E.; Platanias, Leonidas C.
Abstract: Mnk kinases (Mnk1 and 2) are downstream effectors of Map kinase pathways and regulate phosphorylation of eukaryotic initiation factor 4E. Engagement of the Mnk pathway is critical in acute myeloid leukemia (AML) leukemogenesis and Mnk inhibitors have potent antileukemic properties in vitro and in vivo, suggesting that targeting Mnk kinases may provide a novel approach for treating AML. Here, we report the development and application of a mutation‐based induced‐fit in silico screen to identify novel Mnk inhibitors. The Mnk1 structure was modeled by temporarily mutating an amino acid that obstructs the ATP‐binding site in the Mnk1 crystal structure while carrying out docking simulations of known inhibitors. The hit compounds display activity in Mnk biochemical and cellular assays, including acute myeloid leukemia progenitors. This approach will enable further rational structure‐based drug design of new Mnk inhibitors and potentially novel ways of therapeutically targeting this kinase. Abstract : Mnk kinases (Mnk1 and 2) are downstream effectors of Map kinase pathways and regulate phosphorylation of eukaryotic initiation factor 4E. Engagement of the Mnk pathway is critical in acute myeloid leukemia (AML) leukemogenesis and Mnk inhibitors have potent antileukemic properties in vitro and in vivo, suggesting that targeting Mnk kinases may provide a novel approach for treating AML. Here, we report the development and application of a mutation‐based induced‐fit in silico screen to identify novel Mnk inhibitors. The Mnk1 structure was modeled by temporarily mutating an amino acid that obstructs the ATP‐binding site in the Mnk1 crystal structure while carrying out docking simulations of known inhibitors. The hit compounds display activity in Mnk biochemical and cellular assays, including acute myeloid leukemia progenitors. This approach will enable further rational structure‐based drug design of new Mnk inhibitors and potentially novel ways of therapeutically targeting this kinase.